Work, motherhood and women's affective well-being - Carina Keldenich (Review of Economics of the Household, 2021)
This paper analyzes how motherhood and labor market status interact in their relationship to women's affective well-being using Day Reconstruction Method data from the United Kingdom Time Use Survey 2014–2015. The dataset contains information on how much time respondents spent on their various daily activities as well as how much they enjoyed each episode. This information is aggregated into a measure of an individual's affective well-being on a given day by calculating the mean of the reported enjoyments weighted by the duration of the respective episode. Results indicate a positive and significant correlation between motherhood and affective well-being. However, this relationship decreases in magnitude and even becomes insignificant in some specifications when controlling for labor market status. This could indicate that an increase in the likelihood of being in a labor market status associated with higher affective well-being mediates the positive relationship between motherhood and affective well-being. Women working part-time, self-employed women, homemakers and women on maternity leave are shown to have higher affective well-being than full-time employees. Furthermore, the time spent on and enjoyment experienced in employment related activities appears to be a key driver of many results in this study. Contrasting results in specifications using a measure of life satisfaction highlight the importance of considering affective as well as cognitive well-being.
Keywords: D13; I30; J22; 330; Affective well-being; Labor market status; Motherhood; Family economics; Day reconstruction method